2002
DOI: 10.1128/jb.184.7.1958-1965.2002
|View full text |Cite
|
Sign up to set email alerts
|

Physical Map of the Linear Chromosome of Streptomyces hygroscopicus 10-22 Deduced by Analysis of Overlapping Large Chromosomal Deletions

Abstract: The chromosomal DNA of Streptomyces hygroscopicus 10-22, a derivative of strain 5102-6, was digested with several restriction endonucleases and analyzed by pulsed-field gel electrophoresis (PFGE). Digestions with AseI gave 11 fragments with a total length of ca. 7.36 Mb. The AseI sites were mapped by analysis of overlapping chromosomal deletions in different mutants and confirmed by Southern hybridizations using partially digested genome fragments and linking cosmids as probes. PFGE analysis of DNA with and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…General growth media and growth conditions for E. coli and Streptomyces strains and standard methods for handling E. coli and Streptomyces in vivo and in vitro, such as preparation of plasmid and chromosome DNAs, construction of a Streptomyces genomic library in E. coli, transformation, and Southern hybridization, were as described previously (23,32), unless stated otherwise. DNA samples were prepared, digested, and separated by PFGE as described previously (31). DNA sequencing was performed using ABI Prism BigDye Terminator Cycle Sequencing Ready Reaction kits from Perkin-Elmer Applied Biosystems.…”
Section: Methodsmentioning
confidence: 99%
“…General growth media and growth conditions for E. coli and Streptomyces strains and standard methods for handling E. coli and Streptomyces in vivo and in vitro, such as preparation of plasmid and chromosome DNAs, construction of a Streptomyces genomic library in E. coli, transformation, and Southern hybridization, were as described previously (23,32), unless stated otherwise. DNA samples were prepared, digested, and separated by PFGE as described previously (31). DNA sequencing was performed using ABI Prism BigDye Terminator Cycle Sequencing Ready Reaction kits from Perkin-Elmer Applied Biosystems.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, three putative regulatory genes were identified, with two at the end of, and one flanking, the cluster. Since S. hygroscopicus 10-22 is much more difficult to manipulate genetically than S. hygroscopicus 5008 (Pang et al, 2002;Qin et al, 1994), here we used strain 5008 as a model to investigate the roles of these three regulatory genes in the biosynthesis of cyclothiazomycin. We proved that the cluster is functional in S. hygroscopicus 5008 and we showed that one of the regulatory genes, SHJG8833, is essential for cyclothiazomycin biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Filamentous soil bacteria, Streptomyces, are unusual in carrying an 8-9 Mb linear chromosome: [1][2][3][4][5][6][7] the genome project for Streptomyces coelicolor A3(2), a model strain for Streptomyces genetics, has been recently completed. 8) Streptomyces species are also known to frequently have linear plasmids, which range from 12 to 1700 kb in size.…”
mentioning
confidence: 99%